Pengaruh Modal, Bahan Baku dan Teknologi Terhadap Produksi Industri Furniture Kayu di Kecamatan Denpasar Barat - PramaYoga, I Wayan Wolfgang (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 6 (2022): VOL 11 NO 6, JUNI 2022 [2045-2480]DO - 10.24843/EEP.2022.v11.i06.p06, 2022)
Furniture is an item that is not only an accessory or a display at home but can be used as a complement to the activities of the residents of the house. The development of the furniture industry is urgently needed to support economic sectors. This study aims to analyze the effect of capital, raw materials and technology simultaneously and partially on the production of the wood furniture industry in West Denpasar District. The sampling method used was simple random sampling with a total sample size of 42. The data analysis technique used was multiple linear regression analysis. The results showed that capital, raw materials and technology simultaneously had a significant effect on the amount of production in the Furniture Industry in West Denpasar District. Partially, capital and technology have a positive and significant effect, while raw materials have a positive and insignificant effect on the production of the wood furniture industry in West Denpasar